Unravelling the fluorescence and semiconductor properties of a new coronene:TCNB charge transfer cocrystal polymorph. Issue 40 (24th September 2021) - Mandal, Arkalekha; Kim, Youngmee; Kim, Sung-Jin; Park, JaeHong
Abstract : The charge transfer-based red emission and expected ambipolar semiconductor properties of a new coronene : TCNB (2 : 3) donor–acceptor cocrystal polymorph are elucidated. Abstract : Charge transfer cocrystallization with an electron rich donor (D) and electron deficient acceptor (A) is a useful method to prepare luminescent organic electronic materials. The electronic nature and photoluminescence property of charge transfer cocrystals are dependent on the choices of donor and acceptor as well as on the supramolecular network. Herein, we report a new polymorph of coronene : TCNB (2 : 3) charge transfer cocrystal that has unique crystal packing with infinite mixed D–A stacks separated by finite A–D–A triads. The new coronene:TCNB polymorph is red emissive ( λ max ≈ 640 nm) with a photoluminescence quantum yield ≈ 5%. Theoretical calculations predict an ambipolar semiconductor nature owing to the electron transport along the infinite D–A stack and hole transport between the coronene molecules of adjacent A–D–A triads in the new cocrystal polymorph. The roles of the supramolecular architecture and the frontier molecular orbitals of donor/acceptor in dictating the optical and electronic properties were elucidated by theoretical studies.